UBI4, the polyubiquitin gene of Saccharomyces cerevisiae, is a heat shock gene that is also subject to catabolite derepression control - Watt, R; Piper, P.W (Molecular & general genetics, 1997)
Carbon and nitrogen regulation of UBI4, the stress-inducible polyubiquitin gene of Saccharomyces cerevisiae, was investigated using a UBI4 promoter-LacZ fusion gene (UBI4-LacZ). Expression of this gene in cells grown on different media indicated that the UBI4 promoter is more active during growth on respiratory than on fermentable carbon sources but is not subject to appreciable control by nitrogen catabolite repression. UBI4-LacZ expression was virtually identical in cells having constitutively high (ras2, sra1-13) or constitutively low (ras2) levels of cyclic AMP-dependent protein kinase activity, indicating that this kinase does not exert a major influence on UBI4 expression. Catabolite derepression control of the UBI4 promoter was confirmed by measurements of UBI4-LacZ expression in hap mutant and wild-type strains before and after transfer from glucose to lactate. Mutagenesis of the perfect consensus for HAP2/3/4 complex binding at position -542 resulted in considerable reduction of UBI4 promoter derepression with respiratory adaptation in HAP wild-type cells and abolished the reduced UBI4-LacZ derepression normally seen when aerobic cultures of the hap1 mutant are transferred from glucose to lactate. This HAP2/3/4 binding site is therefore a major element contributing to catabolite derepression of the UBI4 promoter, although data obtained with hap1 mutant cells indicated that HAP1 also contributes to this derepression. The HAP2/3/4 and HAP1 systems are normally found to activate genes for mitochondrial (respiratory) functions. Their involvement in mediating higher activity of the UBI4 promoter during respiratory growth may reflect the contribution of UBI4 expression to tolerance of oxidative stress.